ST2L Transmembrane Receptor Expression: An Immunochemical Study on Endarterectomy Samples. - Andrea Marzullo; Francesca Ambrosi; Mirjam Inchingolo; Fabio Manca; Fiorella Devito; Domenico Angiletta; Annapaola Zito; Pietro Scicchitano; Marco Matteo Ciccone (PLoS ONE)
Background ST2 (suppression of tumorigenity) has been described as a receptor for the interleukin-33, a member of the IL-1 family of cytokines. It is associated to coronary artery disease, all-causes mortality and cardiovascular mortality. Aims The present study was designed to assess the immunohistochemical expression of the ST2 receptor (ST2L/Il-1R) in atherosclerotic plaques of formalin fixed paraffin-embedded internal carotid arteries of patients with and without cerebro-vascular symptoms. Methods and results The study involved 41 cases (23 asymptomatic and 18 symptomatic). All the clinical and morphological parameters examined were uniformly distributed between the two groups, with a mild predominance of degree of calcification in asymptomatic cases (p = 0.01). ST2L expression was found to be more evident as a membrane pattern in macrophages when observing carotid atherosclerotic plaques of symptomatic patients, rather than in asymptomatic patients' plaques (77.7% vs 39.1%; p = 0.015), and its expression was particularly remarkable in VI type plaque (AHA). Significantly, ST2L was marked by the endothelium of neoangiogenetic vessels on the shoulder region of the plaque, but not (apart from a few cases) in the endothelium covering the residual lumen of the vessel. Conclusions The ST2L immunohistochemical expression was for the first time investigated in a large number of human carotid atherosclerotic plaques, as for its pattern of distribution in the different plaque cell populations. Furthermore, ST2L was particularly remarkable on macrophages, as a membrane pattern, of symptomatic patients' plaque. Considering our data, we hypothesize that ST2L/IL33 axis could drive the mechanism of plaque development and eventually rupture.